Response of the Tribal Farmers on Adoption of Vermiculture: An Avenue for Livelihood Improvement - Mishra, B.P.; Kanwat, Manish; Chandra, Anup; Kumar, P. Suresh; Kumar, Sanjeev; Tripathi, A.K. (Indian Journal of Extension Education, 2021)
“Waste Management” is not at all a less dignified work. Paradigm shift is the need of present time to look wastes as valuable Resource materials for production of vermicompost, biogas, renewable energy and recycling of metals in NEH Region particularly Arunachal Pradesh. The study was designed to know the extent of adoption of different practices of vermiculture technology recommended by the scientists and to find out the adoption gap in various practices with the sample of 120 respondents who were selected purposively from West Siang district, Basar sub-division. Maximum adoption gap (51.67%) was found in following the practice of preparing beds without treatment. The adoption gap of 45.84 per cent existed for the recommended practice of regular watering for maintaining temperature and humidity in the bed. Therefore, every stakeholders including Government functionaries should focus to spread the worthy technology at grass root level through skilled training programmes, method demonstration and exposure visits on scientific production of vermicomposting help to remove the constraints mentioned above.
Keywords: Vermiculture; tribal; earthworms; adoption gap; West Siang; Basar; Arunachal Pradesh